PENERAPAN KINEMASTER SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA KELAS IV DIMASA COVID-19 - fitri yanti fitri yanti; Adam Mudilillah (As-Sibyan, 2021)
The Kinemaster application is an application that people use to edit various animated photos or videos. This application aims to make it easier for teachers to create a variety of learning media. Almost everyone uses applications for work that function as the use of this sophisticated technology. The relationship of learning Indonesian is very closely related. The relationship is to teach learning materials, teachers need technology media to help them explain the material. This application is the best in its use. Doing the practice of making media using the kinemaster application must look at the situation, not all learning media are made through the application, it can also be manually depending on our views and see the situation and condition of students in learning. A wise teacher must be able to use technology wisely too, where the teacher is able to use technology well.